2 (x+8) =3 (x-9)
2x+16=3x-27 (distributive)
16=x-27 ( subtract 2x)
x= 43 (add 27)
2007-01-25 05:49:49
·
answer #1
·
answered by 7
·
0⤊
1⤋
Simplifying
2(x + 8) = 3(x + -9)
Reorder the terms:
2(8 + x) = 3(x + -9)
(8 * 2 + x * 2) = 3(x + -9)
(16 + 2x) = 3(x + -9)
Reorder the terms:
16 + 2x = 3(-9 + x)
16 + 2x = (-9 * 3 + x * 3)
16 + 2x = (-27 + 3x)
Solving
16 + 2x = -27 + 3x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-3x' to each side of the equation.
16 + 2x + -3x = -27 + 3x + -3x
Combine like terms: 2x + -3x = -1x
16 + -1x = -27 + 3x + -3x
Combine like terms: 3x + -3x = 0
16 + -1x = -27 + 0
16 + -1x = -27
Add '-16' to each side of the equation.
16 + -16 + -1x = -27 + -16
Combine like terms: 16 + -16 = 0
0 + -1x = -27 + -16
-1x = -27 + -16
Combine like terms: -27 + -16 = -43
-1x = -43
Divide each side by '-1'.
x = 43
Simplifying
x = 43
2007-01-25 05:58:59
·
answer #2
·
answered by Anonymous
·
0⤊
1⤋
Multiply thru:
2x+ 16 = 3x-27
Subtract 2x then add 27 to both sides:
x = 16+27 = 43
2007-01-25 05:51:47
·
answer #3
·
answered by kellenraid 6
·
0⤊
1⤋
x=43
2007-01-25 05:52:12
·
answer #4
·
answered by Ha!! 2
·
0⤊
1⤋
2(x+8)=3(x-9)
2x+16=3x-27
16+27=3x-2x
x=43
2007-01-25 06:02:18
·
answer #5
·
answered by karikool 3
·
0⤊
0⤋
2x+16 = 3x-27
43 = x
{43}
2007-01-25 05:49:26
·
answer #6
·
answered by aficionado210 2
·
0⤊
1⤋
2x+16=3x-27
2x-3x+16=3x-3x-27
-x+16=-27
-x+16-16=-27-16
-x=-43
x=43
2007-01-25 06:11:57
·
answer #7
·
answered by Dave aka Spider Monkey 7
·
0⤊
0⤋
?
2007-01-25 05:54:31
·
answer #8
·
answered by blinkoc 2
·
0⤊
1⤋